HFE mutations in patients with iron overload in Santa Catarina: a cross-sectional study - Cristiane Manfé Pagliosa; Vivian Karla Brognoli Franco; Thiago Sousa Matias; Bruno Vieira Dias; Andrea Thives de Carvalho Hoepers (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Investigating the frequency and characteristics of iron overload cases with HFE gene mutation is crucial, given the population-level risks associated with excessive iron. OBJECTIVE: To determine the frequency of HFE mutations in patients with iron overload in Santa Catarina, Brazil. DESIGN AND SETTING: A cross-sectional study of patients with iron overload at the Ambulatory Department of the Centro de Hematologia e Hemoterapia de Santa Catarina (Hemorrede-HEMOSC) in Santa Catarina. METHODS: HFE genotype frequencies were determined, and a division were made between carriers of HFE -C282Y/C282Y mutations and carriers of other HFE-non-C282Y/C282Y mutations, according to each region of Santa Catarina. Binary logistic regression was used for association between sex and age with genetic mutation trait. RESULTS: Among the 1,022 patients, 10.4% had secondary hemochromatosis, and 89.6% were evaluated for iron overload due to hereditary hemochromatosis (HH). Of these, 367 underwent genetic testing, which revealed HFE mutations in 77.3%. Most patients with HFE mutations had non-C282Y/C282Y-hemochromatosis, especially H63D/WT (> 39%), regardless of the Santa Catarina region. The frequency of C282Y/C282Y was higher in the West (20.9%) and North (28.3%) regions. Adjusted association analysis showed that men have an increased chance of hemochromatosis when involving 'non-C282Y/C282Y' mutations (OR: 2.77; 95% CI: 1.60–6.608). CONCLUSIONS: The data show the magnitude and characteristics of iron overload cases with HFE mutations in Santa Catarina. As most patients referred for treatment have H63D mutation, we suggest further studies to assess whether other factors, including dietary habits and mandatory iron fortification policies, contribute to iron overload or HH manifestation.